Revealing the contribution of astrocytes to glutamatergic neuronal transmission - Cuellar-Santoyo, Ares Orlando; Ruiz-Rodríguez, Victor Manuel; Mares-Barbosa, Teresa Belem; Patrón-Soberano, Araceli; Howe, Andrew G.; Portales-Pérez, Diana Patricia; Miquelajáuregui Graf, Amaya; Estrada-Sánchez, Ana María (Frontiers in Cellular Neuroscience, 2023)
Research on glutamatergic neurotransmission has focused mainly on the function of presynaptic and postsynaptic neurons, leaving astrocytes with a secondary role only to ensure successful neurotransmission. However, recent evidence indicates that astrocytes contribute actively and even regulate neuronal transmission at different levels. This review establishes a framework by comparing glutamatergic components between neurons and astrocytes to examine how astrocytes modulate or otherwise influence neuronal transmission. We have included the most recent findings about the role of astrocytes in neurotransmission, allowing us to understand the complex network of neuron-astrocyte interactions. However, despite the knowledge of synaptic modulation by astrocytes, their contribution to specific physiological and pathological conditions remains to be elucidated. A full understanding of the astrocyte's role in neuronal processing could open fruitful new frontiers in the development of therapeutic applications.